Pile configuration optimization on the design of combined piled raft foundations - Asefa, Birhanu; Assefa, Eleyas; Pantelidis, Lysandros; Sachpazis, Costas (My University, 2021)
This paper examines the impact of different pile configurations and geometric parameters on the bearing capacity and the settlement response of a combined pile–raft foundation system utilizing FLAC3D software. The configurations considered were: (1) uniform piles (denoted as CONF1), (2) shorter and longer piles uniformly distributed on the plan view of the raft (CONF2), (3) shorter piles at the center and longer piles at the edge of the raft (CONF3), and (4) longer piles at the center and shorter piles at the edge of the raft (CONF4). In the same framework, different pile diameters and raft stiffnesses were examined. The piles are considered to float in a cohesive–frictional soil mass, simulating the thick cohesive soil deposit found in Addis Abeba (Ethiopia). During simulation, a zero-thickness interface element was employed to incorporate the complex interaction between the soil elements and the structural elements. The analyses indicate that the configuration of piles has a considerable effect on both the bearing capacity and the settlement response of the foundation system. CONF1 and CONF3 improve the bearing capacity and exhibits a smaller average settlement than other configurations. However, CONF3 registers the highest differential settlement. On the other hand, the lowest differential settlement was achieved by the CONF4 configuration; the same configuration also gives ultimate load resistance comparable to those provided by either CONF1 or CONF3. The study also showed that applying zero-thickness interface elements to simulate the interaction between components of the foundation system is suitable for examining piled raft foundations problem.
Keywords: FLAC3D; Interface elements; Numerical modeling; Pile configurations; Piled-raft foundation